Quantifying viable cells - Morrey, John D.; Lowry, John (Utah : Taped Technologies, 1992)
Described the ability to count the number of cells. Includes prepare hemocytometer, load hemocytometer, count cells microscopically, identify viable cells and alternate counting methods.
Copy available in DVD format
Keywords: Microbial viability counts